Effect of hydroponic and peat-free media in transplant production of Rudbeckia hirta varieties under different photoperiodic lighting and their photosynthetic parameters - Antal, G.; Kurucz, E.; Koncz, K.; Kaszás, L.; Fári, M. G. (International Journal of Horticultural Science, 2021)
The purpose of this research was to determine the effects of varieties, different light conditions (short day, long day, natural short day with light pollution), and different growing media (perlite, peat-free, peat-based, aeroponics system) on Rudbeckia hirta plant production under controlled conditions (greenhouse). The morphological effects of each treatment (photoperiodic lightings and media) on different Rudbeckia varieties determined at 11 weeks-old ’Napfény’, ’Toto Gold’, ’Autumn Colors’, ’Prairie Sun’ and 16 weeks-old ’Napfény’. Plantlets received 12 hours daylight did not initiate flowers, remained stage of the leaf rosette in case of all varieties. The 14 hours light treatment in the aeroponics system and the same treatment in perlite and control (natural short day with 14 hours light pollution) plantlets had developed inflorescences or flower buds. The inflorescence axis of ‘Napfény’ was appeared at 13 weeks under long-day conditions, with 1.7 (perlite) - 2.7 (aeroponics) flower buds in 16 weeks. ’Toto Gold’, ’Autumn Colors’, ’Prairie Sun’ varieties developed inflorescences at 8 weeks, 14 hours aeroponics system resulted in the most of flower buds (’Toto Gold’: 6.5, ’Autumn Colors’: 3.25,’Prairie Sun’: 4.8 flower buds) at 11 weeks. Long daylight manipulation could be minimized crop times and achieved flowering potted plants at 11 weeks. The peat-based and peat-free media effect was observed on ‘Autumn Colors’. The number of leaves of peat-free ‘Autumn Colors’ transplants (16.8-20.3) was significantly higher than peat-based media (13.5-15.5). Other morphological parameters were not affected by the media treatments.